Effects of Insecticide-Treated Nets and Stagnant Water on the Risk of Malaria: A Meta-Analysis - Atika Dwi Minawati; Dinda Nur Asri Mutiara Ramadhani; Siti Damayanti; Yovita Galuh Eka Ariska; Bhisma Murti; Anggun Fitri Handayani (Journal of Epidemiology and Public Health, 2023)
Background: Malaria infection is a global public health problem that causes major morbidity worldwide. Stagnant water is one of the risk factors for malaria, insecticide-treated nets are one of the interventions that can prevent malaria. This study aims to estimate the magnitude of the effect of using insecticide-treated nets and stagnant water around the house on the risk of malaria. Subjects and Method: This study was conducted using a systematic review and meta-analysis with PICO, Population: children. Intervention: insecticide-treated mosquito nets and stagnant water. Comparison: without insecticide-treated nets and no stagnant water. Result: incidence of malaria. By searching for articles in 3 databases namely PubMed, Google Scholar, and Science Direct published from 2016 to 2023, by entering the following keywords insecticide-treated bed nets” OR “ITN” AND “stagnant water” OR “STAGNA” AND “Malaria” AND “Cross-sectional” AND “Multivariate Analysis”. Articles were selected using the PRISMA flow and data analysis using the Review Manager 5.3. Results: There are 13 articles using a cross-sectional study design with a total sample of 5,793 children from Indonesia, Cameroon, Nigeria, and Ethiopia which have gone through a systematic review and meta-analysis. Processed data showed that children who used insecticide-treated nets had a 0.65 times lower chance of contracting malaria compared to those who did not use insecticide-treated nets (aOR= 0.65; 95% CI= 0.41 to 1.01; p= 0.060). Children who live in an environment where there is stagnant water have a 4.10 times chance of getting malaria compared to children who live in an environment where there is no stagnant water and this is statistically significant (aOR= 4.10; 95% CI= 2.80 to 6.03; p <0.001). Conclusion: Insecticidal mosquito nets reduced the incidence of malaria, and stagnant water increased the incidence of malaria. Keywords: insecticide-treated nets, stagnant water, STAGNA, children Correspondence: Atika Dwi Minawati. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir Sutami No.36, Kentingan, Jebres, Surakarta, 57126, Central Java. Email: dwiminawatiatika@gmail.com. Mobile: +625212613303.